2020
DOI: 10.1088/1361-6595/aba113
|View full text |Cite
|
Sign up to set email alerts
|

Transients using low-high pulsed power in inductively coupled plasmas

Abstract: Pulsed inductively coupled plasmas (ICPs) are widely deployed in the fabrication of semiconductor devices. Pulse repetition frequencies of up to tens of kHz are commonly used during plasma etching for the high power densities they generate during the pulse-on period, and for their unique chemistries during the pulse-off period. The use of highly attaching halogen gases produces low electron densities during the pulse-off period, and these low densities can result in instabilities, E-H transitions and ignition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Maximum value, range of values plotted, and units for contour labels are indicated in each image. These results are from Qu et al 65 …”
Section: Review Of Plasma Modeling Techniquessupporting
confidence: 64%
See 2 more Smart Citations
“…Maximum value, range of values plotted, and units for contour labels are indicated in each image. These results are from Qu et al 65 …”
Section: Review Of Plasma Modeling Techniquessupporting
confidence: 64%
“…These results are from Krüger et al 64 Plasma properties from a hybrid model of ICP are shown in Fig. 16 from a paper by Qu et al 65 Instead of the Monte Carlo module, Kolobov and Arslanbekov 66 coupled the spatially dependent Boltzmann equation solver to a fluid plasma model. Two-term approximation was used to reduce the number of dimensions.…”
Section: Hybrid Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is determined by the electromagnetic skin depth. 64) The dynamics of power matching to pulsed ICPs of Ar/Cl 2 mixtures of tens of mTorr pressure using fixed-component impedance matching networks were investigated. 65) This early power coupling enables a more rapid ramp-up in the plasma density while being mismatched during the inductively coupled (H)-mode later in the pulse.…”
Section: 5mentioning
confidence: 99%
“…Then they used high-low pulsed power to adjust the minimum plasma density, which reduces ignition delay and enhances plasma stability. [9] Han et al [10] measured the time-resolved magnetic field, electron density, and electron temperature for pulsed argon plasma. They found that a "ring" shape density profile appears at the initial stage of discharge, which then evolves to a peak in the middle of the chamber.…”
Section: Introductionmentioning
confidence: 99%